FUZZY FONKSİYONLARININ İSTATİSTİKSEL YAKINSAKLIĞI - CEYLAN, VİSALİ (Fırat Üniveristesi, 2020)
Bu tezin ilk bölümünde konunun tarihsel gelişimi verildi. İkinci bölümde ise bir kümenin doğal yoğunluğu, istatistiksel yakınsaklığı ve Cesàro toplanabilme ile ilgili temel tanım ve teoremler verildi. Üçüncü bölümde, fuzzy küme tanımı, bazı cebirsel özellikleri ve fuzzy sayı üzerindeki cebirsel işlemler, fuzzy sayılar kümesinin üzerinde tanımlanan metriğin yapısından bahsedildi. İlaveten fuzzy sayı dizisi ve bu dizilerin noktasal istatistiksel yakınsaklığı kavramları detaylı olarak verildi. Dördüncü bölümde fuzzy fonksiyon dizilerinin dereceden noktasal istatistiksel yakınsaklık kavramının bazı özellikleri incelendi ve dereceden kuvvetli noktasal yakınsaklık ile arasındaki ilişkiler verildi.

In the first part of this thesis, historical improvement of subject is given. In the second part, basic definitions and theorems related to natural density and statistical convergence of a set and Cesàro summability are given. In the third chapter, definition of fuzzy set, some algebraic properties of fuzzy set, algebraic operations on fuzzy numbers and the structure of metric defined on fuzzy set are mentioned. In addition, by giving the fuzzy number sequence and the basic properties of these sequences, the statistical convergence of the fuzzy number sequences and the pointwise statistical convergence of the fuzzy function sequences are given in detail. In the fourth part, some features of the concept of ? ? pointwise statistical convergence of fuzzy function sequences with ? .degree are examined. And the relation of it with strongly ? p ? pointwise convergence with ? .degree is examined.
Statistical convergence of fuzzy functions
Keywords: Matematik